2010
DOI: 10.1111/j.1440-1746.2009.05980.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal are present in human extrahepatic bile ducts

Abstract: This study demonstrates for the first time that ICC are present in human extrahepatic bile ducts where they are more densely aggregated than in the gallbladder. This cellular network is likely to be involved in biliary tract motility and its related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
0
27
1
Order By: Relevance
“…ICLCs expressing CD34 but not c-kit have also been observed in human detrusor [Rasmussen et al, 2007] and gut [Pieri et al, 2008] where immunoelectrolabeling confirmed the ultrastructure of CD34+ cells as ICLCs. In several spontaneously active smooth muscle tissues, c-kit-expressing ICLCs appear to be the dominant type [Popescu et al, 2005;Biers et al, 2006;Lang et al, 2007;Lavoie et al, 2007;Ahmadi et al, 2010] including sheep mesenteric lymphatics [McCloskey et al, 2002]. We observed, however, only a subset of lymphatic ICLCs to express c-kit and this is of interest when speculating upon a physiological role for ICLCs in the TD.…”
Section: Interstitial Cajal-like Cellscontrasting
confidence: 48%
See 1 more Smart Citation
“…ICLCs expressing CD34 but not c-kit have also been observed in human detrusor [Rasmussen et al, 2007] and gut [Pieri et al, 2008] where immunoelectrolabeling confirmed the ultrastructure of CD34+ cells as ICLCs. In several spontaneously active smooth muscle tissues, c-kit-expressing ICLCs appear to be the dominant type [Popescu et al, 2005;Biers et al, 2006;Lang et al, 2007;Lavoie et al, 2007;Ahmadi et al, 2010] including sheep mesenteric lymphatics [McCloskey et al, 2002]. We observed, however, only a subset of lymphatic ICLCs to express c-kit and this is of interest when speculating upon a physiological role for ICLCs in the TD.…”
Section: Interstitial Cajal-like Cellscontrasting
confidence: 48%
“…Interstitial Cajallike cells (ICLCs), or telocytes as they are also known, are morphologically distinct from smooth muscle cells (SMCs) and while they can be identified by expression of proteins specific to them (such as the receptor tyrosine kinase c-kit), ultrastructural assessment by transmission electron microscopy is the unequivocal method for identifying and distinguishing ICLCs from other interstitial cells, such as fibroblasts [Faussone-Pellegrini and Popescu, 2011]. Several spontaneously active smooth musclecontaining tissues expressing c-kit-positive ICLCs have been found in human [Metzger et al, 2004;Metzger et al, 2008;Ahmadi et al, 2010] and animals [Lang et al, 2007;Lavoie et al, 2007], but to date there is only a single report of lymphatic ICLCs from a study of sheep mesenteric lymphatics [McCloskey et al, 2002]. Given that human TD is known to be spontaneously contractile and the suggestion that ICLCs could contribute to this function in other smooth muscles, we proposed that ICLCs could be present in the wall of the human TD.…”
Section: Introductionmentioning
confidence: 99%
“…ICCs are found in the biliary systems of both guinea pigs and humans [23,24]. Gallbladder motility involves various regulatory mechanisms, such as gallbladder smooth Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry muscle and nervous circuit activity, including gallbladder ICCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the last century, several studies have found that ICLCs exist in the gut of both human beings and animals, and they have been detected in the esophagus, stomach, small intestine, large bowel, ileum, and colon [16][17][18]. More recently, studies have found that ICLCs are distributed in the gallbladder and extrahepatic biliary duct of both guinea-pigs and humans [18][19][20][21]. Gallbladder motility is regulated by various mechanisms, for instance, the activity of the gallbladder smooth muscle and the nervous circuit, which includes gallbladder ICLCs [15].…”
Section: Discussionmentioning
confidence: 99%